Persepsi Ex-Followers @gitasav terhadap Personal Branding-nya sebagai Education-Influencer pasca Pernyataan “Childfree” di Instagram - Silalahi, Giofanny D Br; Sudradjat, Ratih Hasanah (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Gita Savitri's statement regarding the issue of "childfree" on Instagram received various pro and con comments from internet users, especially followers of @gitasav, not even a few of them decided to unfollow @gitasav. The purpose of this study is to find out how the perception of ex-followers of @gitasav of her personal branding as education-influences after content and statements "childfree" on Instagram. This research is qualitative using a descriptive approach, which focuses on the eight main concepts of personal branding (8 laws of personal branding) by Montoya (2002). As a result, the perception of ex-followers @gitasav of her personal branding as education-influencers after content and statements about "childfree" don’t meet all elements in the main concept of personal branding by Montoya (2002), because it doesn’t meet the elements of Personality (The Law of Personality), Visibility (The Law of Visibility), Unity (The Law of Unity), and Goodwill (The Law of Goodwill).
Keywords: Education-Influencer; Ex-Followers; Instagram; Personal Branding